PELATIHAN BUDIDAYA PORANG SEBAGAI BAHAN PANGAN PREMIUM UNTUK MENINGKATKAN PENDAPATAN PETANI DI DESA SEKOCI KECAMATAN BESITANG KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Fitria Fitria; Juita Rahmadani Manik; Misril Fuadi; Muhammad Alqamari; Muhammad Said Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Porang (Amorphophallus oncophyllus Prain.) or often referred to as iles-iles belongs to the Araceae family and is one of the biological richness of Indonesian tubers. As a plant that produces carbohydrates, fats, proteins, minerals, vitamins, and dietary fiber, porang plants have long been used as food ingredients and exported as industrial raw materials. However, the plant has not been widely cultivated. Farmers generally only take and use plants that grow wild in the forest, in the fields under bamboo clumps, along riverbanks and mountain slopes. The Community Partnership Program is implemented in Lifeboat Village, District Besitang, Langkat Regency with partners consisting of citrus farmer groups. increase income. The method used to achieve the goals of this service is to conduct counseling or socialization of porang cultivation. The expected target is for partners to be able to cultivate porang as well as understand the benefits of porang plants for alternative food crops and can increase farmers' income so as to reduce food shortages in sustainability. The activity carried out is by distributing porang seeds in the form of frogs.